Derive the third equation of motion: v2 - u2 = 2as

Answer:

For getting the third law of motion equation, we use both of the equations of motion

S = ut + 1/2at2__________(1)

v = u + at _____________ (2)

t = (v – u)/a

Substitute the value of t in equation (1)

S = ut + 1/2at2

 

\(S = u\frac{(v-u)}{a}+\frac{1}{2}a(\frac{v-u}{a})^{2}\)

 

2aS = 2u(v − u) + (v − u)2

2aS = 2uv − 2u2 + v2 − 2uv + u2

2aS = v2 − u2

v2 = u2 + 2aS

Was this answer helpful?

  
   

3.5 (35)

Upvote (36)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question